Unnoticed ingestion of magnetic balls mimics acute appendicitis - Amr Moussa; Mohamed Gouda; Mohamed Jallouli (Elsevier, 2022)
Magnetic object ingestion is rare; however, it is important to be considered and recognized by physicians. Its incidence is expected to be 3.06 cases per 100000 children per year but during the last decade this number has grown fivefold owing to the growing popularity of magnetic toys. Although a single FB may pass spontaneously and uneventfully through the digestive tract, the ingestion of multiple magnetic can cause serious morbidity due to proximate attraction through the intestinal wall.In everyday clinical practice, physicians combine their clinical suspicion of acute appendicitis (AA) with laboratory tests findings and imaging studies to make a final diagnosis. CT scan can be useful in some cases to avoid per operative surprise.We report a case of an 8 years -old child who his admitted for query acute appendicitis. Radiological investigation shows three magnets ball at the right iliac fossa with air fluid level without any signs of perforations. Taking up the clinical history, the patient seems reliable and does not remember having ingested these balls. Colonoscopy fails to remove all the magnets. At surgery we found two perforations one at the terminal ilium and the other on the lateral side of cecum with perforation of the mesoappendix and inflamed appendix. An appendectomy was done with primary closure of both perforations.